Parturition and postpartum dietary change altered ruminal pH and the predicted functions of rumen bacterial communities but did not alter the bacterial composition in Holstein cows - Kim, Yo-Han; Kimura, Atsushi; Sugino, Toshihisa; Sato, Shigeru (Frontiers in Veterinary Science, 2022)
We investigated the temporal dynamics of ruminal pH and the composition and predicted functions of the rumen bacterial community in Holstein cows during the periparturient period. Eight multiparous Holstein cows (body weight; 707.4 ± 29.9 kg, parity; 3.6 ± 0.6) were used for continuous reticulo-ruminal pH measurement, among which five were also used for bacterial community analysis. Rumen fluid samples were collected at 3 weeks before and 2 and 6 weeks after parturition, and blood samples were collected 3 weeks before and 0, 2, 4, and 6 weeks after parturition. After the parturition, reduction in the 1-h mean reticulo-ruminal pH was associated with a significant (P < 0.05) increase in total volatile fatty acid concentration. However, with the exception of a significant change in an unclassified genus of Prevotellaceae (P < 0.05), we detected no significant changes in the compositions of major bacterial phyla or genera or diversity indices during the periparturient period. On the basis of predicted functional analysis, we identified a total of 53 MetaCyc pathways (45 upregulated), 200 enzyme commissions (184 upregulated), and 714 Kyoto Encyclopedia of Genes and Genomes orthologs (667 upregulated) at 6 weeks postpartum that were significantly (P < 0.05) different to those at 3 weeks prepartum. Among the 14 MetaCyc pathways (P < 0.05) in which pyruvate is an end product, PWY-3661 [log2-fold change (FC) = 5.49, false discovery rate (FDR) corrected P < 0.001] was the most highly upregulated pyruvate-producing pathway. In addition, P381-PWY [adenosylcobalamin biosynthesis II (aerobic); FC = 5.48, FDR corrected P < 0.001] was the second most upregulated adenosylcobalamin (Vitamin B12)-producing pathway. In contrast, PWY-2221 (FC = −4.54, FDR corrected P = 0.003), predominantly found in pectinolytic bacteria, was the most downregulated pathway. Our findings indicate that changes in rumen bacterial community structure are not strictly associated with transitions in parturition or diet; however, we did observe changes in reticulo-ruminal pH and the metabolic adaptation of predicted functional pathways. Consequently, predictive analysis of postpartum functional pathways may enable us to gain insights into the underlying functional adaptations of bacterial communities in Holstein cows during the periparturient period.